Estimated total production value, economic value of pollination (EVP) for the entire country and within each biome domain. Values refer to the leading crops in the 2019 harvest. 1Source: IBGE. - Willams Oliveira (21442562) (2025)
Estimated total production value, economic value of pollination (EVP) for the entire country and within each biome domain. Values refer to the leading crops in the 2019 harvest. 1Source: IBGE.